NORMAL INDUCED FUZZY TOPOLOGICAL SPACES - Saha, Apu Kumar; Bhattacharya, Debasish (Italian Journal of Pure and Applied Mathematics, 2015)
The motto of the present treatise is to introduce and characterize the concept of n-infy induced fuzzy topological spaces generated by normal lower semi-continuous functions. Examples of n-infy induced fuzzy topological spaces are given and its properties are studied. Interrelationship between the newly defined induced spaces and their corresponding topological spaces are examined.